GALO:A New Intelligent Task Scheduling Algorithm in Cloud Computing Environment - K. Jasim Mohammad, Omer (International Journal of Engineering and Technology, 2018)
Cloud communication technology is Internet-based computing, where shared resources, software, information, are provided to computers and devices on-demand. They guarantee a way to share distributed resources and services that belong to different organizations through virtualization technology. Cloud has announced a modern idea by deploying one application which offers variety and a lot of services to a number of cloud-users at the same time, however, it suffers from scheduling and workload problems. This paper proposed a cloud computing task scheduling algorithm based on greedy algorithm and Antlion Optimizer algorithm. The main goal of this algorithm is to reduce the make-span and the total cost of the tasks and execution time. This paper suggested the objective share-search function of the make-span and costs of the tasks in order to improve the initialization of the pheromone, the greedy algorithm and the pheromone update method in the antlion algorithm. Also, this context illustrates the analytical study between almost used scheduling algorithms and the proposed algorithm. Theoretically, the proposed algorithm provides a more flexible and guarantee a solution to solve the problem of task scheduling in the cloud computing environment.Â Â